Assessment of Readiness for Electronic Medical Record Implementation in the Inpatient Unit of Port Hospital, Jakarta, Indonesia - Ivonia Kenahin Bahi; Putra, Daniel Happy; Sonia, Dina; Fannya, Putery (Universitas Airlangga, 2025)
This study aims to assess Port Hospital Jakarta’s readiness to implement Electronic Medical Records (EMR) in inpatient units using the Doctor’s Office Quality Information Technology (DOQ-IT) method. EMR systems are essential in modern healthcare, enhancing efficiency, accuracy, and data security while ensuring compliance with government regulations, such as the Ministry of Health Regulation No. 24 of 2022. Port Hospital Jakarta has implemented EMR only in outpatient services, while inpatient services rely on conventional medical records. This study employed a descriptive quantitative approach, collecting primary data from 127 respondents using a non-probability purposive sampling technique. Data were analyzed using Microsoft Excel to assess organizational readiness in two key aspects: organizational alignment and capacity. The findings indicate that the hospital’s inpatient units fall within Range II regarding organizational alignment, with a score of 17.19, categorized as